Hydride formation mechanisms in Zr-containing amorphous alloys during sample preparation and atom probe tomography - Yipyintum, Chetarpa; Lee, Ji Yeong; Suh, Jin-Yoo; Lohwongwatana, Boonrat (Carl Hanser Verlag GmbH & Co., 2023)
Hydride formation in Zr-containing amorphous alloys as an experimental artifact was investigated utilizing atom probe tomography, transmission electron microscopy, and focused ion beam with normal and cryogenic conditions. The amount of hydrogen existing in the atom probe specimens decreased significantly by utilizing focused ion beam milling under cryogenic condition. Also, the formation of hydride was confirmed by diffraction pattern analysis in the remaining tip of the specimen after the atom probe tomography experiment. With those collected pieces of evidence, sources of hydrogen in the atom probe tomography were discussed.